2012
DOI: 10.1016/j.molbiopara.2011.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Developmental regulation of gene expression in the absence of transcriptional control: The case of kinetoplastids

Abstract: Kinetoplastids, including the human pathogens Trypanosoma brucei, Trypanosoma cruzi and Leishmania, are the only known organisms that do not regulate the transcription of protein coding genes transcribed by RNA polymerase II. Yet, profound changes in gene expression are induced by many different external stimuli and stresses, the extreme example are cascades of changes in gene expression initiated by differentiation triggers that ultimately and irreversibly result in the massive morphological and metabolic cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
133
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(141 citation statements)
references
References 198 publications
0
133
0
2
Order By: Relevance
“…Other members of the kinetoplastid EIF4E family, TbEIF4E1 through TbEIF4E4, respond to stress by forming cytosolic granules (Kramer et al 2008, and comparable behavior has been noted for TbE5 (data not shown). In a group of organisms that predominantly lack regulation of gene/protein expression at the level of transcription initiation (Martínez-Calvillo et al 2010;Alsford et al 2012;Kramer 2012), the presence of a putative cytosolic capping enzyme suggests a specific role for RNA processing and/or regulation by the TbE5 complexes. The link between cytosolic mRNA metabolism and the motility-defect phenotypes could lie in TbEIF4E-mediated control of RNA regulons associated with motility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other members of the kinetoplastid EIF4E family, TbEIF4E1 through TbEIF4E4, respond to stress by forming cytosolic granules (Kramer et al 2008, and comparable behavior has been noted for TbE5 (data not shown). In a group of organisms that predominantly lack regulation of gene/protein expression at the level of transcription initiation (Martínez-Calvillo et al 2010;Alsford et al 2012;Kramer 2012), the presence of a putative cytosolic capping enzyme suggests a specific role for RNA processing and/or regulation by the TbE5 complexes. The link between cytosolic mRNA metabolism and the motility-defect phenotypes could lie in TbEIF4E-mediated control of RNA regulons associated with motility.…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of transcription initiation by RNA polymerase II is minimal (Martínez-Calvillo et al 2010;Günzl 2012). The control of protein abundance and function during the parasite lifecycle is mediated predominantly through post-transcriptional mechanisms such as mRNA stability and availability, translational efficiency, post-translational modification, and protein stability (Clayton and Shapira 2007;Fernandez-Moya and Estevez 2010;Kramer 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, gene expression has been shown to change dramatically throughout the complex life cycles of these parasites (Haile and Papadopoulou 2007;Rochette et al 2008;Nilsson et al 2010;Siegel et al 2010). Regulation of mRNA decay rates through interactions of RNA-binding proteins (RBPs) with cis-acting sequences in 3 ′ UTRs of trypanosomatid transcripts is central in determining the fate of mRNAs and thus fine-tuning developmental gene expression (McNicoll et al 2005;Bringaud et al 2007;Haile and Papadopoulou 2007;Haile et al 2008;Müller et al 2010b;Kramer 2012;Clayton 2013). Several RBPs, such as zinc finger proteins, Alba-domain proteins, and Pumilio (PUF) proteins, have been found to regulate mRNA stability in trypanosomatids (Clayton 2013;Dupé et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Essa inusitada forma de organização genômica resulta em genomas muito densos devido à ausência quase total de íntrons e a ciclos celulares de tempos mais reduzidos (Kramer, 2012).…”
Section: Regulação Da Expressão Gênica Em Tripanossomatídeos Por Tranunclassified